The Role Of Halal Certification And P-Irt From A Legal Perspective Towards Strengthening Legality And Competitiveness Dhiandra Brownies In Malang - Rokiyah Rokiyah; Ane Fany Novitasari; Sri Hudiarini; Evi Fajriantina Lova (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to examine the role of Halal Certification and P-IRT (Household Food Industry Certification) from a legal perspective in enhancing the legality and competitiveness of Dhiandra Brownies, a Micro, Small, and Medium Enterprise (MSME) in Malang. The research employs a qualitative approach using juridical-sociological and normative methods, supported by legal and literature analysis. The findings reveal that both certifications are not only formal legal requirements but also strategic assets that strengthen product credibility, consumer trust, and market access. Halal Certification, based on Law No. 33 of 2014, and P-IRT, regulated by the Ministry of Health Regulation No. 23 of 2017, reflect state recognition of product safety and religious compliance. However, the study also identifies several implementation challenges, including low legal literacy among MSME actors, overlapping institutional authorities, and high certification costs. These obstacles hinder the inclusive realization of legal empowerment. The study concludes that Halal and P-IRT certifications should be repositioned as part of an integrated strategy for MSME development—one that ensures legal certainty, promotes economic justice, and enhances sustainable competitiveness through regulatory reform and institutional synergy.